Depiction of Mount Meru, the sacred mountain - Temples of India Project Team (Jio Institute, 2024)
The painting in the inner/upper circle in the ceiling of the mandapa (pillared hall) has Mount Meru, the sacred mountain, depicted in the cosmic universe. There are five stages, from bottom to top, that symbolizes the centre of the world, which is surrounded by Jambudvipa, the earthly world. After every Tirthankara is born, he meets with God by ascending all these stages. Mount Meru painting illustrated the journey of the Tirthankara; hence, the centre of every stage has a Tirthankara sitting in a padmasana (lotus pedestal) pose. The inscription reads, ‘Meru Parbat.’